Governance Structures: Dependability And Efficiency Of The Waqf Institutional System In Malaysia - Julia Mustaffa; Mohd Yaziz Bin Mohd Isa; Zulkifflee Mohammed (Journal of Economics and Business Aseanomics (JEBA), 2022)
Waqf lands have the potential to bring in billions of dollars in income for Muslim communities provided that they are successfully developed and managed. In the past, there was no established legal framework for the management of waqf in Malaysia. As a result, waqf land and assets were managed in an inefficient and disorganized manner. The State Islamic Religious Council (SIRC) in Malaysia oversees the waqf administration and is responsible for the legislation in Malaysia that is related to waqf. The SIRC in its role as the sole trustee is in charge of overseeing all aspects of waqf matters. It was made more difficult in Malaysia because there are 13 states and federal territories and each of them has its waqf regulation and as a result, there are different challenges. In addition, the law and enactment of waqf in each state are uniquely distinct from the legislation and enactment in the other states correspondingly. The disparities in size, the varying numbers of waqf properties, and other aspects are the core of these problems. If these Waqf properties were efficiently handled, it would be the ideal solution to the challenge of increasing the social and economic position of the Muslim community. Unfortunately, the waqf institutions in Malaysia do not seem to be capable of playing a proactive role in promoting the economic growth and overall development of Muslims in Malaysia. The purpose of this study is to better understand the challenges in governance, especially in the administration, management, and development of waqf in Malaysia